Thursday

July 24, 2014

July 24, 2014

Posted by **tony** on Saturday, January 15, 2011 at 6:28pm.

- math -
**Reiny**, Saturday, January 15, 2011 at 7:31pm(x + 2)(3x - 1) = 0

take it from there

**Related Questions**

Math - factoring - Solve by factoring: 1.) x^2 - x - 12 = 0

math - 6. Solve by factoring. mē + 8m + 7 = 0 (1 point)8, 7 7, 1 *7, 1 7, 1 7...

Math-Factoring - Hey I need help factoring 5x^4-180x^2. I'm used to factoring ...

math 123 - solve the equation by factoring 3x^2-8x-3=0 (3x+1)(1x-3)=0 Now solve ...

gr 10 math - Solve by factoring. a) x^2 + 3x - 28 = 0 (x+7)(x-4) d)x^2 + 8x + 16...

Math - I cant figure out how to solve this problem Solve by Factoring: 5x^2-32=-...

Math - 2x(x+3) = 0 Is there a way to solve that using the below methods? ...

math - Solve by Factoring 2a^2 - 3a = -5

math - solve by factoring 2a^2+3=7a Thanks

math - Solve by factoring: 2a^2-3a= -5